2009
DOI: 10.1007/s11605-008-0790-6
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Lymphadenectomy and Surgical Outcome of Upper Thoracic Esophageal Squamous Cell Carcinoma

Abstract: Based on logistic regression analysis, T3/T4 tumors and recurrent nerve node metastasis were possible risk factors for cervical node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…An et al [9] classified 217 patients receiving 3-field nodal scavenge into 4 groups, i.e., no LM, having LM in Zone 1, in Zone 2, and in Zone 3, and found that there were signifi cant differences in 5-year survival rate among the patients in the 4 groups. The outcome of the study by Shimada et al [15] was similar to that from An's study. Zhang et al [19] conducted a retrospective analysis of 1,146 EC patients and found that the 5-year survival rates were respectively 59.79%, 33.38%, 14.28%, 6.26% and 2.98% in EC patients with 5 different grades of disease which included the number of the metastasized nodes of 0, 1, 2, 3 and ≥ 4.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…An et al [9] classified 217 patients receiving 3-field nodal scavenge into 4 groups, i.e., no LM, having LM in Zone 1, in Zone 2, and in Zone 3, and found that there were signifi cant differences in 5-year survival rate among the patients in the 4 groups. The outcome of the study by Shimada et al [15] was similar to that from An's study. Zhang et al [19] conducted a retrospective analysis of 1,146 EC patients and found that the 5-year survival rates were respectively 59.79%, 33.38%, 14.28%, 6.26% and 2.98% in EC patients with 5 different grades of disease which included the number of the metastasized nodes of 0, 1, 2, 3 and ≥ 4.…”
Section: Discussionsupporting
confidence: 72%
“…Most authors have believed that 3-fi eld scavenge could increase the survival rate of EC patients [13][14][15] . However, Watanabe et al [16] found that the 5-year survival rate of EC patients was higher in the group with the modern 2-fi eld lymphadenectomy than in the other 2 groups, suggesting that the key point of the extended lymphadenectomy is the precise dissection of the lymph nodes surrounding the bilateral RLNs area, instead of a scavenge of the lymph nodes surrounding the neck.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the RLN lymph nodes are important in the prediction of metastases to distant lymph nodes during thoracic esophageal cancer. The positivity of RLN lymph nodes for metastases indicates a wider range of lymph node metastases [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in cases of unilateral RLN lymph node metastasis, bilateral supraclavicular lymph node dissection should be recommended [ 3 ]. Furthermore, recurrent nerve node metastasis is a possible risk factor for cervical node metastasis [ 4 ]. However, in clinical practice, we found that ultrasounds can be attenuated by air that is present inside the trachea and bronchi and that this limits the use of EUS in the detection of metastases in the para-esophageal lymph nodes, especially in instances of RLN lymph node metastases that are close to the trachea.…”
Section: Introductionmentioning
confidence: 99%
“…In squamous cell carcinoma, patients with cervical esophageal cancer undergo proximal esophagectomy with cervical and upper mediastinal lymphadenectomy using a cervical approach, whereas those with thoracic esophageal cancer undergo total esophagectomy with three-field lymphadenectomy using a transthoracic approach. [6][7][8][9][10] However, there is no agreement on the operative procedure and extent of lymphadenectomy for esophageal squamous cell carcinoma located at the cervicothoracic junction (CT-ESCC). Thus, we retrospectively studied the distribution of metastasis in lymph nodes resected at surgery and the recurrence after surgery for patients with CT-ESCC and investigated the extent of lymphadenectomy that is necessary.…”
mentioning
confidence: 99%